Toughening strategies in adhesive joints. (February 2019) - Maloney, Kevin; Fleck, Norman
Abstract: Concepts are explored for increasing the Mode I toughness of an epoxy-based adhesive joint in a double-cantilever beam. First, a line of cylindrical holes (termed "stop holes") are introduced at regular intervals along the bondline to arrest crack growth periodically. The diameter and spacing of the stop holes are varied, and it is found that the presence of stop holes increases the macroscopic fracture toughness of an adhesive joint by up to 50%. Second, a woven copper wire mesh is embedded within the adhesive bondline. Large-scale crack bridging of the mesh across the adhesive layer is promoted by adding polytetrafluoroethylene strips on alternating faces of the adherends, at regular intervals along the bondline. A cohesive zone model, as calibrated by the measured traction versus separation response of a tensile butt joint, adequately simulates the failure response of the mesh-reinforced specimens. These results suggest that bondline flaws, voids, de-bonded regions and foreign material can induce higher macroscopic toughness for a macroscopic crack in an adhesive joint.